Parameter-robust linear quadratic Gaussian technique for multi-agent slung load transportation - Lee, Hae-In; Yoo, Dong-Wan; Lee, Byung-Yoon; Moon, Gun-Hee; Lee, Dong-Yeon; Tahk, Min-Jea; Shin, Hyo-Sang (Elsevier, 2017)
This paper copes with parameter-robust controller design for transportation system by multiple unmanned aerial vehicles. The transportation is designed in the form of string connection. Minimal state-space realization of slung-load dynamics is obtained by Newtonian approach with spherical coordinates. Linear quadratic Gaussian / loop transfer recovery (LQG/LTR) is implemented to control the position and attitude of all the vehicles and payloads. The controller's robustness against variation of payload mass is improved using parameter-robust linear quadratic Gaussian (PRLQG) method. Numerical simulations are conducted with several transportation cases. The result verifies that LQG/LTR shows fast performance while PRLQG has its strong point in robustness against system variation.
Keywords: Unmanned aerial vehicle; Slung-load dynamics; Linear quadratic Gaussian; Loop transfer recovery; Parameter-robust control